Reactive Astrocytes Promote ALS-like Degeneration and Intracellular Protein Aggregation in Human Motor Neurons by Disrupting Autophagy through TGF-β1 - Pratibha Tripathi (Stem Cell Reports, 2017)
Summary: Amyotrophic lateral sclerosis (ALS) is a fatal and rapidly progressing motor neuron disease. Astrocytic factors are known to contribute to motor neuron degeneration and death in ALS. However, the role of astrocyte in promoting motor neuron protein aggregation, a disease hallmark of ALS, remains largely unclear. Here, using culture models of human motor neurons and primary astrocytes of different genotypes (wild-type or SOD1 mutant) and reactive states (non-reactive or reactive), we show that reactive astrocytes, regardless of their genotypes, reduce motor neuron health and lead to moderate neuronal loss. After prolonged co-cultures of up to 2 months, motor neurons show increased axonal and cytoplasmic protein inclusions characteristic of ALS. Reactive astrocytes induce protein aggregation in part by releasing transforming growth factor β1 (TGF-β1), which disrupts motor neuron autophagy through the mTOR pathway. These results reveal the important contribution of reactive astrocytes in promoting aspects of ALS pathology independent of genetic influences. : Using long-term co-cultures of reactive astrocytes and human motor neurons, Zhou and colleagues show that reactive astrocytes, regardless of their genetic makeup, are toxic to motor neurons and induce neuronal loss, neurite shrinkage, and axonal and cytoplasmic protein inclusions. Reactive astrocytes promote neuronal protein aggregation partly through enhanced TGF-β1 signaling, which activates mTOR pathway and impairs autophagy in motor neurons. Keywords: ALS, reactive astrocytes, autophagy, TGF-b, mTOR, human motor neurons